Simulating cross-contamination of cooked pork with Salmonella enterica from raw pork through home kitchen preparation in Vietnam - Sinh Dang Xuan; Hung Nguyen-Viet; Phuc Pham Duc; Grace, Delia; Unger, Fred; Nam Nguyen-Hai; Thanh Nguyen Tien; Makita, K. (MDPI, 2018)
Pork is the most commonly consumed meat in Vietnam, and Salmonella enterica is a common contaminant. This study aimed to assess potential S. enterica cross-contamination between raw and cooked pork in Vietnamese households. Different scenarios for cross-contamination were constructed based on a household survey of pork handling practices (416 households). Overall, 71% of people used the same knife and cutting board for both raw and cooked pork; however, all washed their hands and utensils between handling raw and cooked pork. The different scenarios were experimentally tested. First, S. enterica was inoculated on raw pork and surfaces (hands, knives and cutting boards); next, water used for washing and pork were sampled to identify the presence and concentration of S. enterica during different scenarios of food preparation. Bootstrapping techniques were applied to simulate transfer rates of S. enterica cross-contamination. No cross-contamination to cooked pork was observed in the scenario of using the same hands with new cutting boards and knives. The probability of re-contamination in the scenarios involving re-using the cutting board after washing was significantly higher compared to the scenarios which used a new cutting board. Stochastic simulation found a high risk of cross-contamination from raw to cooked pork when the same hands, knives and cutting boards were used for handling raw and cooked pork (78%); when the same cutting board but a different knife was used, cross-contamination was still high (67%). Cross-contamination between was not seen when different cutting boards and knives were used for cutting raw and cooked pork. This study provided an insight into cross-contamination of S. enterica, given common food handling practices in Vietnamese households and can be used for risk assessment of pork consumption.